Legislating Modesty:Classical and Contemporary Debates on State-Enforced Hijab in Islamic Governance - Fouz Zacky; Abdurraafi Abdulgani Serang (MAQOLAT: Journal of Islamic Studies, 2025)
This paper examines the controversial issue of state-enforced hijab within Islamic governance. The debate is pivotal to the discourse on women’s rights within Islamic societies and is intertwined with broader socio-political dynamics such as governance, human rights, and individual freedom. Despite extensive literature on various dimensions of hijab, there remains a gap in analyses that bridge classical Islamic political thought with contemporary socio-political realities. Employing a qualitative textual analysis of classical treatises and modern scholarly debates, this study assesses whether the state holds a legitimate role in mandating hijab. It explores historical enforcement mechanisms and contrasts them with ideological arguments surrounding hijab enforcement in the modern era. The findings reveal that while classical Islamic scholars emphasized the state’s role in upholding public morality, explicit discussions on hijab enforcement are largely absent. Meanwhile, contemporary debates reveal a spectrum ranging from advocacy for state-enforced hijab to moderate and liberal emphases on personal choice and opposition to coercion. The paper proposes a balanced maqasid-based approach, recommending that Islamic governance prioritize inculcating a culture of modesty through education and public engagement over deploying extensive and coercive legal measures.